Agricultural Development and Food Security in Africa The Impact of Chinese, Indian and Brazilian Investments - Cheru, Fantu; Modi, Renu (Africa Now, 2013)
The subject of food security and land issues in Africa has become one of increased importance and contention over recent years. In particular, the focus has shifted to the role new Global South donors - in particular India, China and Brazil - are playing in shaping African agriculture through their increased involvement and investment in the continent. Approaching the topic through the framework of South-South co-operation (SSC), this highly original volume presents a critical analysis of the ways in which Chinese, Indian and Brazilian engagements in African agriculture are structured and implemented. Do these investments have the potential to create new opportunities to improve local living standards, transfer new technology and knowhow to African producers, and reverse the persistent productivity decline in African agriculture? Or will they simply aggravate the problem of food insecurity by accelerating the process of land alienation and displacement of local people from their land? Topical and comprehensive, 'Agricultural Development and Food Security in Africa' offers fresh insight into a set of relationships that will shape both Africa and the world over the coming decades.